2011
DOI: 10.1038/jhh.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

The association between aortic augmentation index and cardiovascular risk factors in a large unselected population

Abstract: The augmentation index (AIx) is a measure of systemic arterial stiffness, and previous studies have demonstrated an association between AIx and risk factors of cardiovascular disease (CVD). However, there is limited knowledge about the age and gender differences of the observed associations. Therefore, the aim of the present study is to examine the association's consistency at different ages and to see if the associations are the same in men and women. This study is based on 3432 subjects from The Copenhagen C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 40 publications
7
41
0
1
Order By: Relevance
“…Previous studies have demonstrated an association between AIx and cardiovascular risk factors, including smoking [6,23]. In our work, the highest BMI corresponds to the former smokers group, which could explain the lower value of PAIx75 in this group because the augmentation index decreases when BMI increases [24].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies have demonstrated an association between AIx and cardiovascular risk factors, including smoking [6,23]. In our work, the highest BMI corresponds to the former smokers group, which could explain the lower value of PAIx75 in this group because the augmentation index decreases when BMI increases [24].…”
Section: Discussionsupporting
confidence: 59%
“…Smoking has been associated with increased arterial stiffness and central hemodynamic indices [3-6]. There is evidence that the ankle-brachial index inversely and linearly correlates with cigarette smoking [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the AIx is simpler as compared to the determination of PWV [24,25]. Previous studies have demonstrated independent prognostic features of this index as a predictor of acute cardiovascular events [26]. The AIx varies depending on heart rate (HR); the AIx adjusted to a standard heart rate of 75 bpm (AIx75) is commonly used (AIx75).…”
Section: Evaluation Of Arterial Stiffness In Patients With Bronchial mentioning
confidence: 99%
“…42 The AIx is commonly accepted as a measure of the enhancement (augmentation) of central aortic pressure by a reflected pulse wave (shown in the second, smaller waveform in Figure 2.12).…”
Section: The Augmentation Indexmentioning
confidence: 99%